2014
DOI: 10.3390/ijms151018131
|View full text |Cite
|
Sign up to set email alerts
|

Thermoase-Derived Flaxseed Protein Hydrolysates and Membrane Ultrafiltration Peptide Fractions Have Systolic Blood Pressure-Lowering Effects in Spontaneously Hypertensive Rats

Abstract: Thermoase-digested flaxseed protein hydrolysate (FPH) samples and ultrafiltration membrane-separated peptide fractions were initially evaluated for in vitro inhibition of angiotensin I-converting enzyme (ACE) and renin activities. The two most active FPH samples and their corresponding peptide fractions were subsequently tested for in vivo antihypertensive activity in spontaneously hypertensive rats (SHR). The FPH produced with 3% thermoase digestion showed the highest ACE- and renin-inhibitory activities. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
8
23
0
Order By: Relevance
“…The FPI suspension was heated to 37 °C and adjusted to pH 8.0 with 0.5 M NaOH. Thermoase GL‐30 was added at 2.5 or 3.0% (based on FPI protein weight) as previously described (Nwachukwu et al, ). Following enzyme addition, the protein digestion was performed for 4 hours with temperature and pH maintained constant using a thermostat‐equipped hotplate and periodic addition of 0.5 M NaOH, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FPI suspension was heated to 37 °C and adjusted to pH 8.0 with 0.5 M NaOH. Thermoase GL‐30 was added at 2.5 or 3.0% (based on FPI protein weight) as previously described (Nwachukwu et al, ). Following enzyme addition, the protein digestion was performed for 4 hours with temperature and pH maintained constant using a thermostat‐equipped hotplate and periodic addition of 0.5 M NaOH, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, in addition to their nutritional value, recent works have indicated the potential use of flaxseed proteins as sources of bioactive peptides, such as angiotensin‐converting enzyme inhibitors and free radical scavengers (Marambe, Shand, & Wanasundara, ; Marambe, Shand, & Wanasundara, ; Udenigwe & Aluko, ). The multifunctional nature of flaxseed protein‐derived peptides is also evident in studies that have demonstrated potential health‐promoting functions, such as antimicrobial (Hwang, Chen, Luo, & Chiang, ), antihypertensive (Doyen et al, ; Nwachukwu, Girgih, Malomo, Onuh, & Aluko, ), calmodulin‐inhibiting (Udenigwe & Aluko, ), anti‐inflammatory (Udenigwe, Lu, Han, Hou, & Aluko, ), antioxidant (Hwang et al, ; Udenigwe, Lu, et al, ), and antidiabetic (Doyen et al, ) properties. Thus, flaxseed protein‐derived peptides can serve as useful ingredients in the production of functional foods and nutraceuticals targeted at preventing and/or delaying the onset of certain human diseases.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results can be interpreted to mean that optimum peptide sizes were produced with the 1% enzyme dose whereas at higher doses, some of the active peptides may have been further hydrolyzed, which reduced renin‐inhibitory ability. In contrast, the renin‐inhibitory activity of flaxseed protein hydrolyzates was increased at higher protease concentrations (Nwachukwu, Girgih, Malomo, Onuh, & Aluko, ). Differences could be due to the lack of similarity between the amino acid composition of chicken skin and flaxseed as well as the specificity of proteases used, both of which would have led to production of peptides that have no common amino acid sequences.…”
Section: Animal Protein Hydrolyzatesmentioning
confidence: 99%